2013
DOI: 10.1002/jts.21830
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Prolonged Exposure Therapy for Veterans With Posttraumatic Stress Disorder

Abstract: Prolonged Exposure (PE) is an evidenced-based psychotherapy for posttraumatic stress disorder (PTSD) that is being disseminated nationally within the U.S. Department of Veterans Affairs (VA) with promising initial results. Empirical evidence, however, regarding the effectiveness of PE for treatment of PTSD in military veterans is limited. Building on previous treatment outcome research, the current study investigated the effectiveness of PE in a diverse veteran sample. One-hundred fifteen veterans were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 49 publications
6
49
1
Order By: Relevance
“…Multiple studies have been conducted with combat veterans in the VA system (Eftekhari et al, 2013;Goodson et al, 2013;Rauch et al, 2009;Tuerk et al, 2011;Yoder et al, 2012). All of the effectiveness studies carried out with vetrans have shown that PE is an effective treatment for PTSD.…”
Section: Psychotherapies For Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have been conducted with combat veterans in the VA system (Eftekhari et al, 2013;Goodson et al, 2013;Rauch et al, 2009;Tuerk et al, 2011;Yoder et al, 2012). All of the effectiveness studies carried out with vetrans have shown that PE is an effective treatment for PTSD.…”
Section: Psychotherapies For Ptsdmentioning
confidence: 99%
“…However, the above effectiveness studies tend to have similar limitations. Studies either tend to have a relatively small sample size (n =115 or lower) (e.g., Goodson et al,2013;Rauch et al, 2009;Tuerk et al, 2011) and/or a pre-post design that does not enable the tracking of treatment non-completers over time (e.g., Eftekhari et al, 2013). Initial PTSD Symptom Severity.…”
Section: Psychotherapies For Ptsdmentioning
confidence: 99%
“…In randomized, controlled trials of PE in veterans, drop-out rates between 23% and 38% have been reported (Schnurr et al, 2007;Eftekhari et al, 2013;Simmons et al, 2013). Recent published analyses of patient charts found drop-out rates ranging from 27% to 44% (Jeffreys et al, 2013;Tuerk et al, 2011;Goodson et al, 2013) for veterans treated with PE by providers hired and trained as trauma specialists in VA specialized PTSD programs. Treatment drop-out has been theorized as a response to the early recounting of the trauma memory in therapy, which initially exacerbates symptoms, activates avoidance mechanisms, and may lead patients to withdraw from treatment (Schnurr et al, 2007;Leiner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 50% of patients achieved the response criterion of 50% reduction in PTSD according to the PTSD Checklist-Military Version[48] after a mean of 11.6 weekly sessions. In a separate report, Goodson and colleagues[49] also found significant benefit with PE among a group of veterans with predominantly combat PTSD. Tuerk et al .…”
Section: Introductionmentioning
confidence: 99%